Is N=40 magic?: an analysis of ISOLTRAP mass measurements - Guénaut, Celine; Herfurth, Frank; Kluge, Heinz-Jürgen (The European physical journal. A, Hadrons and nuclei, 2005)
Recently high-precision mass measurements were performed on Ni, Cu, and Ga isotopes at the triple-trap mass spectrometer ISOLTRAP at ISOLDE/CERN. The relative uncertainty was of the order of 10-8. Data indicate a competition between the sub-shell closure N = 40 and the mid-shell region N = 39 between the well-known magic numbers N = 28 and N = 50.
Gesehen am 03.03.2020